2007
DOI: 10.1021/ja067245h
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Nitrogen Oxides with the Five-Coordinate FeIII(porphyrin) Nitrito Intermediate Fe(Por)(ONO) in Sublimed Solids

Abstract: Detailed experimental studies are described for reactions of several nitrogen oxides with iron porphyrin models for heme/NxOy systems. It is shown by FTIR and optical spectroscopy and by isotope labeling experiments that reaction of small increments of NO2 with sublimed thin layers of the iron(II) complex Fe(Por) (Por = meso-tetraphenylporphyrinato dianion, TPP, or meso-tetra-p-tolylporphyrinato dianion, TTP) leads to formation of the 5-coordinate nitrito complexes Fe(Por)(eta1-ONO) (1), which are fairly stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 54 publications
4
35
0
2
Order By: Relevance
“…18,25 However, it has been reported that the spectra of reduced froms of nitrosyl complexes show the n(NO) peak at much lower wavenumbers. 65,66 The electronic absorption spectral changes observed for trans-[Ru(NO)Cl(1-pramcyH)](PF 6 ) 3 consist of an absorbance decrease at 263 nm with a concomitant increase at 291 nm. The final electronic absorption spectrum is assigned to the trans-[Ru(NO)Cl(1-pramcyH)] 2+ complex.…”
Section: The Cyclic Voltammetry Study Of Trans-[ru(no)mentioning
confidence: 99%
“…18,25 However, it has been reported that the spectra of reduced froms of nitrosyl complexes show the n(NO) peak at much lower wavenumbers. 65,66 The electronic absorption spectral changes observed for trans-[Ru(NO)Cl(1-pramcyH)](PF 6 ) 3 consist of an absorbance decrease at 263 nm with a concomitant increase at 291 nm. The final electronic absorption spectrum is assigned to the trans-[Ru(NO)Cl(1-pramcyH)] 2+ complex.…”
Section: The Cyclic Voltammetry Study Of Trans-[ru(no)mentioning
confidence: 99%
“…DFT computations at the B3LYP/LACVP* level suggest [54] that the nitrito and nitro linkage isomers Fe(P)(ONO) and Fe(P)(NO 2 ) (P = the unsubstituted porphinato dianion) have similar energies with the nitrito species more stable, but only by less than 1 kJ mol −1 . Despite this, the experimental studies showed only the former to be present as the initial product from the reaction of NO 2 with Fe(TPP) or Fe(TTP) in layered solids.…”
Section: The Five-coordinate Nitrito Complexes Of Iron Porphyrinsmentioning
confidence: 99%
“…The room temperature reaction of NO gas with sublimed layers containing pre-formed Fe(Por)(ONO) (Por = TPP or TTP) leads to rapid formation of the familiar nitro-nitrosyl complexes Fe(Por)(NO 2 )(NO) [54]. However, at low temperature (130 K), the reaction nearly quantitatively forms nitrosyl complexes identified as the nitrito isomers Fe(Por)( 1 -ONO)(NO) owing to the characteristic and isotope sensitive nitrosyl and nitrito bands in the vicinity of 1890…”
Section: The Interaction Of Fe(por)(ono) With Nitric Oxidementioning
confidence: 99%
See 2 more Smart Citations